Halal Food Awareness and Halal Certification: Halal Food Purchasing Decisions of Generation Z Muslim Consumers in Urban and Sub-Urban Areas - Normasyhuri, Khavid; Edi, Relit Nur; Pradikta, Hervin Yoki; Anggraeni, Erike (ASAS, 2024)
Abstract: Halal food decisions by Muslim consumers illustrate complex interactions. In urban and suburban areas, generation Z faces a multicultural and pluralistic environment which influences their perspective, including regarding food consumption. Halal food purchasing decisions by Muslim consumers around the world reflect a complex mix of Halal Food Awareness and Halal Certification. The aim of this research is to look at aspects of halal food awareness and halal certificates in making decisions to purchase halal food for Generation Z Muslim consumers in urban and sub-urban areas. The research methodology used in this research is quantitative using SmartPLS 3.0 software. Primary data collection was carried out by taking a sample of respondents, namely generation Z Muslim consumers in Urban and Sub-Urban areas in Lampung Province using a purposive sampling method. A total of 300 samples were used for this research. Data was obtained through the use of Google Form, with indicator assessment carried out using a Likert Scale. The research results show that awareness of halal food and halal certificates influence the decision to purchase halal food among Generation Z Muslim consumers in urban areas in Lampung Province. Awareness of halal food influences the decision to purchase halal food among Generation Z Muslim consumers in Sub-Urban Areas in Lampung Province. Halal certificates do not influence the decision to purchase halal food among Generation Z Muslim consumers in Sub-Urban Areas in Lampung Province.Keywords: Halal Food Awareness; Halal Certificate; Purchasing Decisions; Muslim Consumers;  and Generation Z